2020
DOI: 10.1177/1120700019900987
|View full text |Cite
|
Sign up to set email alerts
|

Traction table versus standard table total hip arthroplasty through the direct anterior approach: a systematic review

Abstract: Background: The direct anterior approach (DAA) for total hip arthroplasty (THA) was originally performed with a supine patient on a specialised traction table, but the approach can also be performed on a standard operating table. Despite cost and safety implications, there are few studies directly comparing these techniques and table choice remains largely surgeon preference. The purpose of this review was to compare the clinical outcomes and complication profiles of traction and standard table DAA for primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 57 publications
1
31
0
2
Order By: Relevance
“…The authors acknowledge the demanding nature of this procedure, especially at the beginning of the DAA learning curve (Tables 3 and 4). [15][16][17] Moreover, although the use of a traction table is not mandatory for primary DAA THA, 18 the contemporary surgical technique has been implemented by the authors while using an specialized traction table.…”
Section: Discussionmentioning
confidence: 99%
“…The authors acknowledge the demanding nature of this procedure, especially at the beginning of the DAA learning curve (Tables 3 and 4). [15][16][17] Moreover, although the use of a traction table is not mandatory for primary DAA THA, 18 the contemporary surgical technique has been implemented by the authors while using an specialized traction table.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed DAA-THA using both a speci c orthopedic table and standard operation table . A systematic review conducted by Sarraj et al [23] that collected 44 studies concluded that speci c orthopedic tables and standard operation tables present similar outcomes and complications. However, intraoperative blood loss, surgical time, and intra-operative fracture rate were greater in the speci c orthopedic table group than in the standard operation table group [23].…”
Section: Discussionmentioning
confidence: 99%
“…Sarraj et al compared DAA with use of a traction bed and a standard operating bed, and concluded that the standard operating bed and traction bed had similar clinical outcomes and complication rates. Using the standard operating bed had more advantages, including reduced blood loss, shorter operating time, and fewer intraoperative fractures rates [19]. Meanwhile, it also has disadvantages such as the need for more assistants, the di culty in the femur exposing, and the possibility of additional soft tissue injury.…”
Section: Discussionmentioning
confidence: 99%